EVALUASI POTENSI INTERAKSI OBAT ANTIDIABETIKA ORAL DI APOTEK PERINTIS KURIPAN BANJARMASIN - Novia Ariani; Erna Prihandiwati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Diabetes mellitus is one of the third highest chronic diseases in the world after hypertension. Diabetes mellitus is the highest disease in the Pioneer Pharmacy Kuripan Banjarmasin. The potential for interaction occurs when a patient takes two or more drugs at the same time with the effect of the interaction being beneficial or harmful or even harmful. This study aims to evaluate the potential interactions of oral antidiabetic drugs for the period January - December 2020. This type of research is non-experimental with retrospective data collection. The number of population according to the inclusion and exclusion criteria was 784 prescription sheets from 1,015 prescription sheets. Samples were calculated using the lameshow formula and proportional random sampling technique. The instrument used is an observation sheet. The data were analyzed using the online Medscape drug interaction checker 2021 literature and the Drug Interaction Fact 2010 literature. The results showed that the number of drug combinations with potential interactions based on the mechanism of action was 149 (39.52%) and based on pharmacodynamics 74 (48.05%), pharmacokinetics 33 (21.43%), and 47 or 30.52 unknowns. %. Meanwhile, based on severity, serious 1 (0.65%), moderate 121 (78.57%), minor 32 (20.78%).